Formulasi reed diffuser kombinasi minyak atsiri kayu manis (Cinnamomomum verum) dan sereh wangi (Cymbopogon nardus) sebagai aromaterapi anti stress - Nurhikma Awaluddin; Sri Wahyuni Awaluddin; Nurjannah Bachri; Sella Septiyani Mointi (Postgraduate, University of Mataram, 2023)
This study aims to determine whether the combination formulation of essential oils between cinnamon and citronella can be used as an aromatherapy reed diffuser preparation that has acted as anti-stress aromatherapy. The method used in this research is an experimental laboratory with a post-test only control group design using mice as test animals. The population used in this study was Cinnamon (Cinnamomum verum) and citronella (Cymbopogon nardus), while the samples used were Cinnamon (Cinnamomum verum) and citronella (Cymbopogon nardus) originating from Antang Market, Makassar City, South Sulawesi. taken in the morning. Data collection was carried out using questionnaires and observation methods. A one-way ANOVA statistical test was used to analyze the obtained data. The results showed that the stability of the Reed Diffuser combination of Cinnamon (Cinnamomum verum) and citronella (Cymbopogon nardus) essential oils in organoleptic testing had a physically and chemically stable odor and color. The hedonic test of the odor produced shows a distinctive odor in all four formulas, but the most preferred is at a concentration of 2:3. In addition, the preparation of Reed Diffuser, a combination of Cinnamon (Cinnamomum verum) and citronella (Cymbopogon nardus) essential oils, is effective as an anti-stress based on the results of tests with regular use.